Switch to hypomania induced by repetitive transcranial magnetic stimulation and partial sleep deprivation added to antidepressant: A case report - Krstić, Jelena; Ilić, Tihomir V. (Vojnosanitetski pregled, 2014)
Introduction. Bipolar depression is often unrecognized and difficult to treat because of two opposite problems: treatment resistance and risk of manic switch. Case report. A 53-year-old female was suffering from unipolar depressive disorder since the age of 36. During a recent major depressive episode pervasive feelings of sadness, lost of interest in activities, severe insomnia and highly expressed somatic anxiety dominated 7 months. After unsuccessful tries with two different antidepressants of adequate doses and duration, slow rate repetitive trascranial magnetic stimulation (rTMS) was started, but the patient stayed at the fixed dose of antidepressant. Partial sleep deprivation (PSD) was additionaly applied twice during these 2 weeks with the idea to boost up, or enhance rTMS treatment response. At the last two rTMS sessions depression obviously meliorated, but the patient also expressed symptoms of hypomania. The therapy of rTMS was stopped, hypomanic symptoms gradually vanished and two weeks after the rTMS treatment the patient was euthymic. Antidepressant was kept on. In a follow-up period of 2 years the diagnose of bipolar affective disorder was definitely established. Conclusion. This case report shows that a combination of slow rate rTMS and partial sleep deprivation in the patient at the fixed dose of antidepressants, have strong synergistic effect even with potential to induce hypomanic switch, that is the first description in the literature to our knowledge.
Keywords: bipolar disorder; diagnosis; differential; depression; antidepressive agents; sleep deprivation; transcranial magnetic stimulation